Religious Education in Sweden: Current Developments and Challenges - Brömssen, Kerstin von (Zeitschrift für Pädagogik und Theologie, 2025)
This article accounts for religious education (RE) in the Swedish national curriculum and syllabi, which currently consists in three sub-areas: "religions and other worldviews", "religion and society", and "ethics and questions of life". Research from the different sub-areas is discussed in order to describe the challenges the subject faces in teaching today. Some of the societal contexts and major school reforms that have contributed to changes in the subject since the 1920s are explained. The article argues that RE is sometimes appreciated but also has weak legitimacy and a rather unclear aim of teaching.